2000
DOI: 10.1002/1096-9861(20001016)426:2<330::aid-cne12>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Odorant molecular length: One aspect of the olfactory code

Abstract: Organic acid odorants of differing carbon number produce systematically different spatial patterns of [(14)C]2-deoxyglucose uptake in the glomerular layer of the olfactory bulb. Because increasing carbon number correlates with progressive increases in several molecular features, including hydrophobicity, length, and volume, we determined which of these properties was most associated with systematic changes in the location of an anterior, dorsomedial module responding to fatty acids. We exposed groups of rats t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 36 publications
8
94
0
Order By: Relevance
“…1) that had not been stimulated by any of the hundreds of odorants examined in our previous studies (Johnson et al, 1998,2005aJohnson and Leon, 2000a,b). Consistent with prior results, increasingly ventral glomeruli tended to respond to longer odorous molecules (Johnson et al, 1999(Johnson et al, ,2004Johnson and Leon, 2000b). Alkanes of greater length than were used in this homologous series probably would not be sufficiently volatile for receptor activation, which may explain why pentadecane stimulated the most ventral region of the bulb.…”
Section: Glomerular Response Patterns May Emerge From a Combination Osupporting
confidence: 85%
See 3 more Smart Citations
“…1) that had not been stimulated by any of the hundreds of odorants examined in our previous studies (Johnson et al, 1998,2005aJohnson and Leon, 2000a,b). Consistent with prior results, increasingly ventral glomeruli tended to respond to longer odorous molecules (Johnson et al, 1999(Johnson et al, ,2004Johnson and Leon, 2000b). Alkanes of greater length than were used in this homologous series probably would not be sufficiently volatile for receptor activation, which may explain why pentadecane stimulated the most ventral region of the bulb.…”
Section: Glomerular Response Patterns May Emerge From a Combination Osupporting
confidence: 85%
“…According to the reliable chemotopic organization previously observed (Johnson and Leon, 2000b;Johnson et al, 1999Johnson et al, , 2002Johnson et al, , 2004Johnson et al, , 2005a, and found here for smaller alkanes, the more dorsal glomerular activation by the longest alkanes in the series was surprising. Given the low vapor concentrations of these large odorants, we considered the possibility that the dorsal responses were due to an odorous contaminant in pentadecane and hexadecane.…”
Section: Minor Impurities Greatly Impact Uptake Patternssupporting
confidence: 79%
See 2 more Smart Citations
“…Some aspects of synthetic coding could begin at the receptor itself, through ligand-ligand interactions with the receptor protein [29]. It is still unclear what constitutes an odorant feature [30,31], although one can assume that features correspond with ideal physiochemical ligands for receptor proteins. Thus, features could vary in their complexity from specific carbon chain lengths and functional groups to, perhaps, specific combinations of these more simple components.…”
Section: Olfactory Sensory Physiologymentioning
confidence: 99%